Single-Phase Bridgeless Zeta PFC Converter with Reduced Conduction Losses - Khan, S.A.; Rahim, N.A.; Bakar, A.H.A.; Tan, C.K. (The Korean Institute of Power Electronics, 2015)
This paper presents a new single phase front-end ac-dc bridgeless power factor correction (PFC) rectifier topology. The proposed converter achieves a high efficiency over a wide range of input and output voltages, a high power factor, low line current harmonics and both step up and step down voltage conversions. This topology is based on a non-inverting buck-boost (Zeta) converter. In this approach, the input diode bridge is removed and a maximum of one diode conducts in a complete switching period. This reduces the conduction losses and the thermal stresses on the switches when compare to existing PFC topologies. Inherent power factor correction is achieved by operating the converter in the discontinuous conduction mode (DCM) which leads to a simplified control circuit. The characteristics of the proposed design, principles of operation, steady state operation analysis, and control structure are described in this paper. An experimental prototype has been built to demonstrate the feasibility of the new converter. Simulation and experimental results are provided to verify the improved power quality at the AC mains and the lower conduction losses of the converter.